Orthodox identification of the Russian population in the Republic of Dagestan. 1985–1999 - О. В. Khalidova (Вестник Майкопского государственного технологического университета)
We have a research idea to show the peculiarities of the development of the Orthodox component in the transitional period of the historical development of our country on the example of the Russian population of the Republic of Dagestan as adherents of Orthodox traditions in the national multiconfessional region. The relevance of the research associated with the transformation of the religious component of Russian people of Dagestan under the influence of globalization and socio-cultural processes of recent decades.A positive effect on the development of the religious component of our society as a whole with a number of features in national regions, in particular, Dagestan have been analyzed. The investigated archival and periodical material and analysis of the empirical data have made it possible to consider the development Orthodox identification in the period 1985–1997. The low growth has been noted. Conclusions have been drawn about the unstable situation of Orthodox parishes due to a number of factors, including the political situation, migration processes among the Russian population, which, in turn, led to the low activity of the clergy, their interaction with the authorities to solve pressing social problems.